Konzeptuelle Integration in der deutschen Idiomatik Kognitiv-semantische Analyse anhand ausgewählter Beispiele Zusammenfassung - Olcha, Monika (Die deutsche Sprache in vielfältigen Forschungsparadigmen. Beiträge polnischer Doktoranden anlässlich der 9. Linguistischen Tagung–Łódź, 09.05.2015, 2016)
The aim of the article is an attempt at interpreting the german idiom in the context die Nägel tief in seinen eigenen Sarg einschlagen as a blend according to the principles of conceptual integration and ruling the theory of conceptual metaphor as the possibility to explain the semantics of this phrase. The primary objective of this publication is the explanation of the chosen example to show mechanics of conceptual integration, the cognitive- semantic analysis of the idiomatic expression in german language in the context and also complicated semantic level in the daily discourse.